Effect of Inclusion Agglomeration and Percolation on the Dynamic Stiffness of Composite Materials with Coated Spherical Inclusions1. Issue 5 (27th December 2013) - Andermatt, Samuel T.; Gusev, Andrei A.; Zschech, Ehrenfried
<x xml:space="preserve">Abstract</x> Using a combination of cross‐validated analytical and numerical tools, we investigate the effect of inclusion agglomeration on the dynamic stiffness of composite materials with coated inclusions. Our results indicate that such composite materials with percolating and agglomerating microstructures can exhibit appealing increases in both stiffness and loss moduli. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>